Clustering Transition in Thermo‐Responsive Micropillars. Issue 6 (29th March 2022) - Kim, Junsoo; Choi, Ji Seong; Lim, Suim; Moon, Seung Eon; Im, Jong‐Pil; Kim, Jeong Hun; Kang, Seong Min
Abstract : Clustering of high‐aspect‐ratio micropillars is a common phenomenon in nature, and has been utilized to build complex and large‐scale microarchitectures. To induce the clustering, the micropillars should be prepared to be metastable, so that they cluster under perturbation, such as the drying of water. Consequently, once micropillars cluster, they cannot de‐cluster spontaneously. This article shows that the micropillars of thermo‐responsive hydrogels can cluster and de‐cluster spontaneously and reversibly by changing the temperature. This behavior is called clustering transition. When the temperature is low, the micropillars swell and become soft. When the temperature is high, the micropillars de‐swell and become stiff. This phase transition alters the lowest energy state of the system, resulting in a reversible clustering transition. To demonstrate, high‐aspect‐ratio micropillars of poly(N‐isopropylacrylamide‐co‐acrylamide) hydrogels are fabricated through a soft‐molding technique. The micropillars show the clustering transition, and the behavior is studied using a thermodynamic model. By controlling the temperature, the micropillars grip and release microparticles on‐demand. Abstract : An array of micropillars made of thermo‐responsive hydrogels spontaneously cluster and de‐cluster depending on the temperature. Such a clustering transition is reversible as each state is energetically stable. The clustering transition is understood by using a thermodynamic model.